Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1021/bi200746t
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanism of Action of β-Hairpin Antimicrobial Peptide Arenicin: Oligomeric Structure in Dodecylphosphocholine Micelles and Pore Formation in Planar Lipid Bilayers

Abstract: The membrane-active, cationic, β-hairpin peptide, arenicin, isolated from marine polychaeta Arenicola marina exhibits a broad spectrum of antimicrobial activity. The peptide in aqueous solution adopts the significantly twisted β-hairpin conformation without pronounced amphipathicity. To assess the mechanism of arenicin action, the spatial structure and backbone dynamics of the peptide in membrane-mimicking media and its pore-forming activity in planar lipid bilayers were studied. The spatial structure of the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
81
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 77 publications
(109 citation statements)
references
References 53 publications
(130 reference statements)
9
81
0
Order By: Relevance
“…We examined all resolved structures of short venom peptides to find possible similarities. We searched the PDB for molecules with folds composed of only ␤-hairpins and found a small number of structures: 3 peptides from spiders, 1 peptide from cones (30 -32), 3 antimicrobial peptides, and 1 hormonelike peptide that suppresses the growth of insects (33)(34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…We examined all resolved structures of short venom peptides to find possible similarities. We searched the PDB for molecules with folds composed of only ␤-hairpins and found a small number of structures: 3 peptides from spiders, 1 peptide from cones (30 -32), 3 antimicrobial peptides, and 1 hormonelike peptide that suppresses the growth of insects (33)(34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…The peptide consists of 21 amino acid residues, two of which are cysteines and form a disulfide bond [6]. Due to the high content of basic amino acid residues and compact β-hairpin amphiphilic structure [7], the peptide can rapidly disrupt the integrity of the bacterial membrane by acting through "toroidal pore" formation [11], and thereby increasing its permeability for various substances [3]. Thus, arenicin-1 can increase the effectiveness of drugs that affect intracellular targets.…”
Section: Methodsmentioning
confidence: 99%
“…Generally, a ␤-hairpin contains one or two disulfide bonds to cyclize the peptide chain. Previous studies have reported that amphipathic ␤-hairpin-like structures or two-strand ␤-sheet conformations had potent antimicrobial properties and high cell selectivity (9,24,35).…”
mentioning
confidence: 99%